Use of Doppler indices in prediction of Acute Fetal Hypoxia - Proposed Staging System - P.T. Jadhav; Rajani Jadhav; Kartik Jadhav; Thilotama Naidu; J.V. Mundewadi; Nitin Tikare (Al Ameen Medical College, 2017)
Background: Till now multiple studies regarding Doppler indices in Obstetrics have concentrated on detection of chronic hypoxia, publications have been silent on early detection of fetal hypoxia before the damage sets in. Objective: To develop a novel, credible staging system for early detection of acute fetal hypoxia and its possible progression. A pilot study was undertaken to accomplish this larger objective. Methods: One hundred and thirty two singleton, uncomplicated, pregnancy between 34 to 42 weeks were included in over 1 year and followed up at a semi urban/ rural setup in Northern Karnataka region at 2 local nursing homes, 1 radiology centre and 1 tertiary care centre. A novel staging system was developed based on available patho-physiological knowledge of vascular Doppler changes secondary to change in LV function and applied with Doppler scan findings to detect and predict fetal distress. Standard statistical tests like p value, Chi square tests, Fischer's tests, and Spearman's correlation coefficient were utilized to come to conclusion. Results: Out of 132 subjects 32 subjects were detected with fetal distress (24.24%). Among those 32 subjects, 30 (22.7%) underwent LSCS and 2 had vaginal delivery. One subject continued pregnancy against medical advice and was later detected with IUFD. Proposed new staging of the AFH when applied showed consecutive increase in percentage of subjects with fetal distress with increase in stage. Stage 4 had a maximum percentage of fetal distress with 7 out of 8 subjects (88%). Similarly stage 0, 1, 2 and 3 had 20%, 16%, 19% and 33% respectively. Statistical significance was found between the different stages of AFH and subjects with fetal distress (p<0.0004). Conclusion: This novel staging method can be used to detect and predict acute fetal hypoxia and can help us in better management of the pregnancy.